2009
DOI: 10.1007/s00270-009-9692-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Associated with Dense and Wedge-Shaped Nephrograms Detected 24 h After Chemoembolization

Abstract: This investigation aimed to evaluate patient characteristics and procedural factors associated with abnormal nephrograms encountered on noncontrast computed axial tomography (CAT) obtained 24-h after transarterial chemoembolization (TACE) for primary and metastatic hepatic malignancies. Sixty hepatic chemoembolization procedures were performed in 29 patients who had a median age of 63 years (range 42-79). The male-tofemale ratio was 16:13. Noncontrast CAT scans were obtained approximately 24 h after TACE as pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…On the other hand, Jakobsen et al [ 24 ] demonstrated persistence of the cortical nephrogram by sequentially timed delayed CT scans and postulated that retention of CM occurred in the proximal tubular cells and was greater for the nonionic dimer, iodixanol, in comparison with nonionic monomers. The HU levels we have observed and those reported by Yamazaki et al [ 11 ] and Monsky et al [ 12 ] are generally much higher. More than 98% of the iodixanol administered should be excreted within the first 24 h.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…On the other hand, Jakobsen et al [ 24 ] demonstrated persistence of the cortical nephrogram by sequentially timed delayed CT scans and postulated that retention of CM occurred in the proximal tubular cells and was greater for the nonionic dimer, iodixanol, in comparison with nonionic monomers. The HU levels we have observed and those reported by Yamazaki et al [ 11 ] and Monsky et al [ 12 ] are generally much higher. More than 98% of the iodixanol administered should be excreted within the first 24 h.…”
Section: Discussionsupporting
confidence: 57%
“…Monsky et al [ 12 ] described wedge-shaped or linear peripheral nephrograms in 24-h delayed CT scans in 23.3% (14/60) of patients having undergone TACE and found a statistically significant ( P = 0.029) relationship with procedure time. These authors postulated that these foci represent segmental ischemia and trapped CM in the tubular lumen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracts of leaves and stems of Petiveria alleaceae showed over 60% reduction in blood glucose concentration one hour after oral administration in male Balb/c mice which had been fasted for 48 hours [21,31,32].…”
Section: Petiveria Alleaceaementioning
confidence: 99%